2016
DOI: 10.3847/1538-4357/833/2/259
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of the Circumgalactic Medium in Red and Blue Galaxies: Results From the Cos-Gass+cos-Halos Surveys

Abstract: We use the combined data from the COS-GASS and COS-Halos surveys to characterize the Circum-Galactic Medium (CGM) surrounding typical low-redshift galaxies in the mass range  *~-M M 10 9.5 11.5, and over a range of impact parameters extending to just beyond the halo virial radius (R vir ). We find the radial scale length of the distributions of the equivalent widths of the Lyαand Si III absorbers to be ∼1 and ∼0.4R vir , respectively. The radial distribution of equivalent widths is relatively uniform for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 106 publications
(195 reference statements)
6
68
2
Order By: Relevance
“…In contrast, the precipitation interpretation simply requires the supernova energy to regulate the recycling rate through subsonic pressure-driven lifting of the CGM. The precipitation interpretation therefore appears to be in better alignment with observations showing that the speeds of CGM clouds are usually sub-Keplerian (e.g., Tumlinson et al 2011;Zhu et al 2014;Huang et al 2016;Borthakur et al 2016) and simulations showing that a large proportion of the baryons that end up in stars have cycled at least once through the CGM (Oppenheimer et al 2010;Anglés-Alcázar et al 2017).…”
Section: Supernova Feedback and The Precipitation Limitsupporting
confidence: 80%
“…In contrast, the precipitation interpretation simply requires the supernova energy to regulate the recycling rate through subsonic pressure-driven lifting of the CGM. The precipitation interpretation therefore appears to be in better alignment with observations showing that the speeds of CGM clouds are usually sub-Keplerian (e.g., Tumlinson et al 2011;Zhu et al 2014;Huang et al 2016;Borthakur et al 2016) and simulations showing that a large proportion of the baryons that end up in stars have cycled at least once through the CGM (Oppenheimer et al 2010;Anglés-Alcázar et al 2017).…”
Section: Supernova Feedback and The Precipitation Limitsupporting
confidence: 80%
“…Obser-chummels@gmail.com vations indicate the presence of cool 10 4 K CGM gas bearing neutral hydrogen and low ionization-potential ions ("low ions") like Mg II and Si II (e.g., Churchill et al 1996;Chen et al 1998;Steidel et al 2010;Gauthier et al 2010;Matejek & Simcoe 2012;Tumlinson et al 2013;Prochaska et al 2014;Werk et al 2014;Johnson et al 2017), as well as warmhot gas (10 5.5 -10 6 K) traced by "high ions" in the form of N V, O VI, and Ne VIII (e.g., Stocke et al 2006;Tumlinson et al 2011;Savage et al 2011;Tripp et al 2011;Meiring et al 2013;Pachat et al 2017;Burchett et al 2018). Observational studies consistently demonstrate large quantities and covering fractions for H I and other low ions in the CGM over many redshifts, environments, and halo masses (e.g., Rudie et al 2012, Borthakur et al 2016).…”
Section: Observations Indicate Substantial Cool Gas In Halomentioning
confidence: 95%
“…Other studies found similar absorbers in a significant fraction of LRG halos at projected distances d ≈ 100 − 500 kpc (Gauthier et al 2010;Huang et al 2016). Furthermore, strong Lyα absorption is common around z ≈ 0.2 early-type galaxies (Thom et al 2012;Tumlinson et al 2013), but at lower levels than in star forming galaxies (Borthakur et al 2016). However, using multiply-lensed QSOs, Zahedy et al (2017) found high column density gas around z = 0.4 − 0.7 ellipticals at projected distances as small as ≈ 3 − 15 kpc.…”
Section: Cool Gas In Elliptical Galaxiesmentioning
confidence: 99%